EVALUATION OF THE PROGRAM OF EDUCATION AND TRAINING FOR PROSPECTIVE PRINCIPLES OF STATE VOCATIONAL SCHOOLS IN RIAU ISLANDS PROVINCE - Refri Yendri; M. Ikhsan; Ernik Yuliana (Jurnal Ekonomi, 2023)
From the results of the author's observations in the field, only 5.5% of 36 public vocational school principals in the Riau Archipelago do not have Saucy and NRKS certificates. There is 1 school principal in Anambas Islands Regency, and 1 person in Tanjungpinang City. While 31% of teachers who already have Saucy certification are available, but only available in Batam City (23%) and Tanjungpinang City (8%), the data suggests that the availability of prospective school principals is not evenly distributed, especially in areas far from the provincial capital. Teachers in areas far from the provincial capital are reluctant to participate in the selection of cute training because of the large costs of transportation and accommodation incurred when attending the cute training. Riau Archipelago Province. Knowing the supporting factors and inhibiting factors in the education and training program for prospective heads of State Vocational High Schools in the Riau Archipelago Province. The theory used in this study is that according to Dunn (2003: 610) policy evaluation is a policy that determines a better direction than the previous one with the following characteristics: 1. Effectiveness, 2. Efficiency 3. Adequacy. 4. Alignment 5. Responsiveness 6. Accuracy". The type of research used is a qualitative approach. Number of informants The informants in this study totaled 11 people consisting of 7 Heads of State Vocational High Schools with State status representing 7 Regencies/Cities in the Riau Archipelago Province, then 1 Head of Development of the Riau Islands Province Education office, 1 Head of LPMP/BPMP (now the Education Quality Assurance Center) Riau Islands Province, 1 person Head of the Personnel Development Division of the Riau Islands Province Education Office, 1 Widyaiswara (a speaker in the Cakep activity). Based on the research analysis results, it can be concluded that the Evaluation of the program of Education and Training for Principal Candidates for State Vocational High Schools in the Riau Archipelago Province has gone well. However, there are still obstacles which are a note for the Riau Islands Provincial Education Office, namely: Lack of regional support through the APBD in implementing the Saucy Education and Training for State Vocational High Schools, this can be seen from the lack of budgeted funds for transportation and pocket money for the Saucy Education and Training participants.